Amil Zakat Menurut Hukum Islam dan Peraturan Perundang-Undangan - Rosadi, Aden (Al-Manahij: Jurnal Kajian Hukum Islam, 2017)
Amil zakah (zakah manager/distributor) is one of supporting pillars to the success of zakah management. From juridical view, it is related to Islamic law, but politically it is close to the state policy especially the zakah management policy. The involvement of the state in zakah management depends on the fundamental issue that makes zakah as part of qad}a>’i> and diya>ni> law. Islamic law that has diya>ni> attribute is very dependent on the religious awareness of Islamic society itself. While the qad}a>’i> law involves certain institutions that have legal power to impose and ensure the enforcement of Islamic law in the society. Therefore, zakah managers require strong authority, because they will deal with the community with various level of faith. It is concluded that the success of zakah management should be supported by three aspects, namely substance, structural, and legal awareness.